The Pragmatic Role Of Meta-Discourse Markers In The Attainment Of Persuasion: A Study Of An Iranian Newspaper Advertisement Headlines - Shahab, Sara; Assadi, Nader (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
The present study aimed at investigating the persuasive role of metadiscourse markers in an Iranian newspaper advertisement headlines; say, Hamshari. To achieve the afore-mentioned purpose, the study adopted Fuertes-Olivera, et. al. (2001)s framework of pragmatic elements of advertising which is, in turn, adapted based on Jakobsonian communication model of the advertising discourse, and Fuertes-Olivera et al. (2001)s framework suggesting different functions of metadiscourse in advertising English. The selected examples showed that while textual metadiscourse helps addressees to interpret headlines within the constraints of genre and epistemology, interpersonal metadiscourse provides a kind of balance between informing and persuading the addressees. Moreover, the findings indicated a variety of metadiscourse strategies used by the advertisers in order to persuade prospective customers, including person markers, hedges, emphatics, endophoric markers and evidents. Regarding pedagogical implications, the present study attempted to broaden the pragmatics of advertising discourse and to stress the important role of metadiscourse in EFL courses.